Efficacy and Safety of Emergent Transcatheter Aortic Valve Implantation in Patients with Acute Decompensated Aortic Stenosis: Systematic Review and Meta-Analysis. (24th December 2021) - Shao, Ruochen; Li, Junli; Qu, Tianyi; Fu, Xiaoying; Liao, Yanbiao; Chen, Mao
Abstract : Introduction . The aim of this systematic review and meta-analysis was to investigate the efficacy and safety of emergent transcatheter aortic valve implantation (TAVI) in patients with decompensated aortic stenosis (AS) by comparing the clinical outcomes with the patients who had received the elective TAVI. Methods . By searching PubMed, EMBASE, and Cochrane databases, we obtained the studies comparing the clinical outcomes of emergent TAVI and elective TAVI. Finally, 14 studies were included. Results . A total of 14 eligible articles with 73, 484 patients were included in this meta-analysis. Emergent TAVI was associated with a higher mortality during hospitalization (HR 2.09, 95% CI [1.39 to 3.14]), 30 days (HR 2.29, 95% CI [1.69 to 3.10]), and 1 year (HR 1.96, 95% CI [1.55 to 2.49]). Consistently, the incidence of acute kidney injury (AKI) (RR 2.48, 95% CI [1.85 to 3.32]), dialysis (RR 2.37, 95% CI [1.95 to 2.88]), bleeding (RR 1.62, 95% CI [1.27 to 2.08]), major bleeding (RR 1.05, 95% CI [1.00 to 1.10]), and 30-day rehospitalization (RR 1.30, 95% CI [1.07, 1.58]) were more common in patients receiving emergent TAVI. No statistical differences were found in the occurrence rate of vascular complications (RR 1.11, 95% CI [0.90, 1.36]), major vascular complications (RR 1.14, 95% CI [0.52, 2.52]), permanent pacemaker (PPM) placement (RR 1.05, 95% CI [0.99, 1.11]), cerebrovascular events (RR 1.11, 95% CI [0.98, 1.25]), moderate to severe paravalvular leakage (PVL) (RR 1.23, 95% [CI 0.94 to 1.61]), and device success (RR 0.99, 95% CI [0.97, 1.01]). Conclusion . Emergent TAVI is associated with some postoperative complications and increased mortality compared with elective TAVI. Emergent TAVI should be implemented cautiously and individually.